TOURISM IN CHINA:AN OVERVIEWOFTHE CONTRIBUTIONS OF SHANGHAITOURISM INDUSTRY TOTHE NATIONALECONOMIC DEVELOPMENT - SAFA, MOHAMMAD SAMAUN (ITB Journal Publisher, LPPM ITB, 2009)
The present study has attempted to investigate the contribution of tourism to various macroeconomic variables of China. Secondary data has been used in the study for the five-year period of time. The findings of the study shows that over the last five years there was a gradual positive growth in tourist receipt, employment, development of supportive industry and so forth except a sharp fall in 2003. The growth in each variable was lower in 2002 than that of 2004. The study has concluded that there was a positive impact of tourism industry on the macroeconomic development of Shanghai.